1998
DOI: 10.3109/10611869808995872
|View full text |Cite
|
Sign up to set email alerts
|

Improved Body Distribution of14C-labelled AZT bound to Nanoparticles in Rats determined by Radioluminography

Abstract: The objective of the present study is to visualize differences in the body distribution between radiolabelled AZT bound to nanoparticles and a control solution. Polyhexylcyanoacrylate nanoparticles were manufactured by emulsion polymerization in the presence of AZT and an ionic emulsifier, bis(2-ethylhexyl) sulfosuccinate sodium. The AZT-control solution was equally prepared, but contained no monomer. The two preparations were administered either by i.v. injection or perorally by gavage. After determined time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…15 Therefore, nanoparticles in the relatively small size range of 100-150 nm are desirable when targeting agents to the liver. The main aim of this study was to achieve optimal incorporation of gentiopicrin and oleanolic acid in NLCs using a film-ultrasonic method to enhance entrapment efficiency and a central composite design for the response surface.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, nanoparticles in the relatively small size range of 100-150 nm are desirable when targeting agents to the liver. The main aim of this study was to achieve optimal incorporation of gentiopicrin and oleanolic acid in NLCs using a film-ultrasonic method to enhance entrapment efficiency and a central composite design for the response surface.…”
Section: Introductionmentioning
confidence: 99%
“…Use of this carrier system, when compared with aqueous drug solution resulted in higher of the drug levels in the Peyer's patches. In another study, polyhexylcyanoacrylate nanoparticles were employed for the delivery of zidovudine (Lobenberg et al, 1998), thus improving its bioavailability. In a distinct experiment, PLGA nanoparticles containing multiple antiretroviral drugs, i.e ritonavir, lopinavir, and efavirenz were formulated and results showed that drugs could be detected in peripheral blood mononuclear cells in vitro for 28 days (Destache et al, 2009).…”
Section: Nanoparticle Mediated Antiretroviral Therapymentioning
confidence: 99%
“…In a distinct experiment, PLGA nanoparticles containing multiple antiretroviral drugs, i.e ritonavir, lopinavir, and efavirenz were formulated and results showed that drugs could be detected in peripheral blood mononuclear cells in vitro for 28 days (Destache et al, 2009). In a study with zidovudine-loaded poly(isohexyl cyanate) nanoparticles, zidovudine was accumulated in the cells of the reticuloendothelial system (Lobenberg et al, 1998). Poly(epsilon-caprolactone) nanoparticles loaded with saquinavir were also successfully used for targeting the phagocytic mononuclear system by modifying the surface of the nanoparticles (Shah & Amiji, 2006).…”
Section: Nanoparticle Mediated Antiretroviral Therapymentioning
confidence: 99%
“…Considerable work has been done to formulate polymerantiviral drug nanoparticles with synthetic or semisynthetic polymers (Dembri et al 2001;Löbenberg et al 1998;Destache et al 2009;Mainardes et al 2009;Sharma and Garg 2010;Duan et al 2010). More recently, studies have shown that polysaccharides are very promising for oral drug delivery due to their affinity for complexing with a variety of drugs which can suppress drug crystallization, their relatively high glass transition temperatures and their biocompatibility (Sandra 2009).…”
Section: Introductionmentioning
confidence: 99%